Why students drink: A study of South African University students’ drinking behaviour - du Preez, R; Pentz, C D; Lategan, B W (South African Journal of Higher Education, 2016)
Little is known about the drinking behaviour of South African university students and education and prevention campaigns are not necessarily based on scientific research results. To change drinking behaviour, it is important to address the drinking motives, alcohol outcome expectancies, and alcohol-related behaviour that hold valence in education and prevention campaigns. The purpose of this study was to gain insight into the drinking behaviour of South African university students, and to make recommendations towards the development of persuasive communications that will address drinking motives and alcohol outcomes. The measurement instruments used in the study included the Alcohol Use Disorder Identification Test (AUDIT), the Drinking Expectancy Questionnaire Revised (DEQ-R), and the Drinking Motives Questionnaire Revised (DMQ-R). Data (n=474) were collected from university students from a single campus in South Africa. The data analyses included independent sample t-tests, ANOVA and partial least squares modelling. The results indicate that students expect an element of tension reduction and an increase in sexual interest when consuming alcohol and that they primarily drink for social and enhancement motives. The influence of positive alcohol outcome expectancies on drinking behaviour is mediated by social and enhancement motives. The study’s findings can be used by universities to develop effective education and responsible drinking programmes.